PENGARUH JIWA KEWIRAUSAHAAN DAN PENGETAHUAN AKUNTANSI TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA MAHASISWA UNHI DENPASAR - Julia Emas Putria Wijaya; Cokorda Gde Bayu Putra (UNHI Press, 2021)
This research has two objectives. First, to determine the effect of an entrepreneurial spirit on the use of accounting information. Second, to determine the effect of accounting knowledge on the use of accounting information. Primary data used is in the form of online questionnaires. The samples in this study used Slovin formula and stratified random sampling method, with a sample of 66 respondents who were students of the 2017 UNHI Denpasar accounting study program. Data analysis used multiple linear regression analysis techniques to answer the problems of this study with help of the SPSS program. Based on the results of the analysis, it was found that the entrepreneurial spirit variable had no effect on the use of accounting information. Meanwhile, accounting knowledge affects the use of accounting information.